FAIRNESS AS INTERPRETIVE DEVICE IN LAW? (AN ANALYSIS OF DISCURSIVE PRACTICES IN THE RECENT CONFLICT ABOUT VOTING RIGHTS IN HONG KONG AND THEIR ANCHORAGE IN ARGUMENTATIVE PRACTICES OF EAST ASIA) - GALDIA, Marcus; LIACI, Antonio (Comparative Legilinguistics, 2016)
Problems related to a conflict about the content of rights are analysed below from the legal-linguistic perspective in the context of the recent dispute about voting rights in Hong Kong. The central legal-linguistic problem that is also the starting point for the analysis of argumentative samples is the question whether legal and legally relevant, yet not strictly legal arguments in such disputes are actually cross-cultural. Furthermore, the question what role, if any, the culture-specific arguments and legal-linguistic devices play in such conflicts is considered as well. With this aim in mind, legal provisions relevant to the conflict and the argumentation used by the opposing sides are explored to find out the legal-linguistically relevant mechanisms that might facilitate the solution of conflicts about the content of rights. Fairness as an interpretive device appears as the most appealing cross-cultural mechanism. Meanwhile, its application in conflict solution mechanisms shows the embeddedness of legal mechanisms in broader social structures that also set limits to the application of purely legal discursive devices. As a result, the analysed conflict appears as an amalgam of legal and extra-legal arguments and non-verbal signs that in their application are cross-cultural. Equally, fairness as an interpretive device in law is deemed cross-cultural, yet also limited in the scope of its application to discursive practices in which it emerges.